Legal Protection for Liability Right Holders in Liability Execution Claims - Anita Christiani; Sundari Sundari; Monica Dewi Widianingsih (Budapest International Research and Critics University, 2022)
Mortgage as a guarantee agreement gives the creditor the right to execute the collateral object himself. The execution of one's own power is regulated in Article 6 of the Mortgage Law. This means that the execution of the Mortgage object can be carried out without the approval of the Debtor or the court fiat. However, in reality the Mortgage Law has not fully provided legal protection to Mortgage Holders in terms of the execution of Mortgage Rights. The purpose of this research is to find out and examine the juridical factors that cause resistance in the execution of Mortgage objects and to find out and examine how the legal protection is given to Mortgage Holders. The type of research in this study uses normative legal research, through a statutory approach. In data management and conclusion drawing is done by thinking process or reasoning deductively. The results of the research and discussion show that the juridical factors that cause resistance in the execution of Mortgage Rights are that the Mortgage Holder does not carry out the proper procedures, namely stating the creditworthiness of bad debtors and refusal of credit restructuring. Economic factors are also the cause of resistance due to the low auction value, the debtor still feels capable of carrying out his achievements and the debtor wants to sell the object of the mortgage. Legal protection for Mortgage Holders as Preferred Creditors has not been fulfilled and the Mortgage Law does not regulate conditions such as resistance and/or lawsuits from Mortgage Providers.